The Influence of English Mastery on the Entrepreneurial Students in Doing Businesses - Ahmad Ghufran Ferdiant; Bariza Nazla Azzulala; Maghfiratul Layla; Ummi Latifah M (ELITE JOURNAL, 2023)
ABSTRACTIndonesia as a developing country continues to increase its cooperation with foreign countries, especially in the field of trade or business. So it is undeniable that the use of English as a means of communication that is widely used with foreign countries greatly affects business. The present study aims to determine whether there is an influence of English mastery on the students of Economics and Islamic Business Faculty of IAIN Madura who have businesses. The research design used in this study was a descriptive quantitative research design. The population were students of the Faculty of Economics and Islamic Business of IAIN Madura. Purposive sampling technique was employed to select 30 samples. Data were collected from the questionnaire distributed to the students. In the present study, validity tests, reliability tests, classical assumption tests, and simple linear regression tests were conducted. The results of it indicated that mastery of English had an effect on the entrepreneurial students. It is very useful for entrepreneurial students and they are suggested to master English well in order to be successful in doing businesses.Keywords: English Mastery, Entrepreneurial Students